Optimal design of coalbed methane wells in mining area with thin to medium thick coal seam group - Ang XU; Shuxun SANG; Xiaozhi ZHOU; Sijie HAN; Jie CHEN; Yunfei FENG; Yi LOU; Zhihua YAN; Wei GAO (Meitan kexue jishu)
In mining areas, utilizing coalbed methane (CBM) wells to extract stress relief coalbed methane from adjacent coal seams is an efficient strategy. To enhance CBM extraction, it is vital to reveal the dynamics of stress and fracture fields evolution and optimization well locations and structure. Taking No. 221015 coalface in Shanjiaoshu coal mine as the study area. By integrating geo-engineering models and engineering data, the stress distribution within and between the overburden was elucidated, the distribution of fracture and the permeability increased zone in the overburden were elucidated, and the well location, structures and enhancement measures were designed. The research demonstrates that: The frequent alternation of lithological properties in the coal measure strata in the study area enhanced the mining influence on overburden. As the key strata progressively fail, the zone located 5−20 meters above the coalface were the fracture zones, in which a large amount of free methane can be migrated and produced across layers, serving as the primary gas source zone of CBM well. The 20−45 meters interval above the coalface belonged to the microfracture zone in the bending subsidence zone, possessing a gas production potential of nearly 2 000 m3/d from adjacent coal seams within a single layer. In this area, stress relief CBM primarily migrates intra-strata and accumulates methane originating from the fracture zone. Optimal well site locations was enclosed by tangential line of the compaction zone along the direction of the coalface and the center line between tangential line of the compaction zone and the return airway, and boundary lines around fractured zones. Meanwhile, the two - or three-stages structure wells with high strength cement cementing and using reaming or screen suspended completion have good stability, which can guarantee long-term extraction work of CBM well. The optimized extraction well scheme provides technical support for achieving a gas production breakthrough of 35000 m3/d from in mining areas of Qianxi region, significantly mitigating the risk of gas outbursts at the coalface. Based on the geological characteristics of multi-layered superimposed CBM systems, the “multi-usage” mode of the vertical well of “multi-layer fracturing and drainage + mining induced stress relief CBM extraction” can serve as a key development direction of “increasing production and efficiency”.